(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2025)
Financial support is a prerequisite and determining factor for the creation, existence, prospects, and directions of development of socio-economic systems at various levels. Scientists are trying to solve the following problems: the essence of financial support as an economic category; its manifestation at various levels of the economy; the components of this system (methods, forms, principles, levers of influence, and control instruments); differences and interrelationships with financing, financial mechanisms, financial relations, financial regulation, financial security, and more. Our systematization of scientific approaches revealed: the predominant use of systemic, process-based, and comprehensive approaches; insufficient or flawed reasoning by researchers; results acceptable for creating a financial support management system. The concept of financial support for business entities (their projects, areas and types of activity, innovative development, crisis management, competitiveness, viability, etc.) consists of a system of principles, goals, subjects, objects, methods, and channels of creation. They are oriented toward certain levels of economic relations and the corresponding financial mechanism for achieving the declared goals. The practical aspects of financial management are closely linked to the state and prospects of national entrepreneurship. The investment climate in the country has been deteriorating recently, as confirmed by businesses and the international community. This is due to military actions, economic destruction, and imperfect actions by the state. Investment lending is being hampered by: the NBU’s high discount rate; risks associated with solvent borrowers; a large share of non-performing loans; and the predominance of short-term deposits. The main investment tool for domestic enterprises has been and remains their own funds (equity capital, profits, depreciation, additional contributions from founders/owners). The reasons for insufficient bank financing are the following: high interest rates; collateral requirements; complex procedures for formalizing agreements; lack of certain financial products; poor credit history or advanced age of the borrower-entrepreneur; operations in frontline territory; insufficient awareness of existing opportunities on the part of the entrepreneur. The activities of government organizations to remove these obstacles and the state of national budget support have been analyzed. A truly effective financial management system is impossible without: the introduction of European standards and norms; harmonization with European legislation; broad access to international assistance without special state support; improving the financial literacy of entrepreneurs; stimulating the introduction of factoring, leasing, crowdfunding, and microfinance, as well as state and private guarantee programs; and strengthening financial transparency requirements.